STRATEGI PEMBELAJARAN BACA-TULIS PEGON DALAM KAJIAN KITAB MABADIUL FIQIH - Putri As-syafi'i, Rizka; Nurul Kawakip , Akhmad; Yaqien, Ainul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pegon literacy plays a crucial role in supporting students' understanding of the yellow books, particularly in the study of Mabadiul Fiqih. However, its implementation in formal educational institutions still faces various obstacles, particularly for students without a background in Islamic boarding schools. This study aims to analyze Pegon literacy learning strategies in Mabadiul Fiqih through a literature study approach. The method used is a qualitative study with a literature review that utilizes secondary data from books, journals, and previous research. The results of the study indicate that students experience linguistic and pedagogical difficulties, such as an inability to understand Pegon structures and limited learning strategies. Effective strategies include a combination of direct and interactive learning, traditional methods such as bandongan and sorogan, and the use of digital media. These strategies contribute to improving the understanding of fiqh concepts. Therefore, integrative and contextual learning strategies are needed to improve Pegon literacy and student understanding.